2022
DOI: 10.1111/jcmm.17645
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of activated vitamin D receptor on radiation‐induced intestinal injury

Abstract: Radiation‐induced intestinal injury (RIII) is a common complication after radiation therapy in patients with pelvic, abdominal, or retroperitoneal tumours. Recently, in the model of DSS (Dextran Sulfate Sodium Salt) ‐induced intestinal inflammatory injury, it has been found in the study that transgenic mice expressing hVDR in IEC (Intestinal Epithelial Cell) manifest highly anti‐injury properties in colitis, suggesting that activated VDR in the epithelial cells of intestine may inhibit colitis by protecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, both studies showed that mice with activated VDR had an increased survival rate compared to wild-type or VDR KO mice 23,38▪▪ . Additionally, in-vitro results showed similar findings that upregulation of VDR could attenuate radiation-induced apoptosis in both IEC-6 and Mode-K cells 23,38▪▪ . Both Lin et al and Li et al .…”
Section: Evidence For Vitamin D In Treating Gastrointestinal Mucositis?mentioning
confidence: 66%
See 3 more Smart Citations
“…Furthermore, both studies showed that mice with activated VDR had an increased survival rate compared to wild-type or VDR KO mice 23,38▪▪ . Additionally, in-vitro results showed similar findings that upregulation of VDR could attenuate radiation-induced apoptosis in both IEC-6 and Mode-K cells 23,38▪▪ . Both Lin et al and Li et al .…”
Section: Evidence For Vitamin D In Treating Gastrointestinal Mucositis?mentioning
confidence: 66%
“… 38▪▪ both demonstrated that VDR knockout (KO) mice and vitamin D-deficient mice significantly increased intestinal damage post-radiation exposure, which was associated with shortened villus height, increased intestinal basal shedding, as well as increased cell apoptosis leading to increased intestinal permeability. Furthermore, both studies showed that mice with activated VDR had an increased survival rate compared to wild-type or VDR KO mice 23,38▪▪ . Additionally, in-vitro results showed similar findings that upregulation of VDR could attenuate radiation-induced apoptosis in both IEC-6 and Mode-K cells 23,38▪▪ .…”
Section: Evidence For Vitamin D In Treating Gastrointestinal Mucositis?mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that radiation-induced intestinal injury is always accompanied with in ammatory response. [41] Therefore, we evaluated the activity of myeloperoxidase (MPO) and the level of pro-in ammatory cytokines in intestinal tissue after different treatment. As depicted in Fig.…”
Section: In Vivo Biodistribution and Radioprotective Effectmentioning
confidence: 99%